2009
DOI: 10.1002/marc.200900261
|View full text |Cite
|
Sign up to set email alerts
|

Layer‐by‐Layer Assembled Nanotubes as Biomimetic Nanoreactors for Calcium Carbonate Deposition

Abstract: Enzyme-loaded magnetic polyelectrolyte multilayer nanotubes prepared by layer-by-layer assembly combined with the porous template could be used as biomimetic nanoreactors. It is demonstrated that calcium carbonate can be biomimetically synthesized inside the cavities of the polyelectrolyte nanotubes by the catalysis of urease, and the size of the calcium carbonate precipitates was controlled by the cavity dimensions. The metastable structure of the calcium carbonate precipitates inside the nanotubes was protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Furthermore, the calcium carbonate-filled hybrid nanotubes also contained Fe 3 O 4 nanoparticles and could be magnetically collected by applying an external magnetic field. 52 …”
Section: Bottom Up Fabrication Of Hybrid Nanotubes Self-assembly mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the calcium carbonate-filled hybrid nanotubes also contained Fe 3 O 4 nanoparticles and could be magnetically collected by applying an external magnetic field. 52 …”
Section: Bottom Up Fabrication Of Hybrid Nanotubes Self-assembly mentioning
confidence: 99%
“…Furthermore, the calcium carbonate-filled hybrid nanotubes also contained Fe 3 O 4 nanoparticles and could be magnetically collected by applying an external magnetic field. 52 Heterostructured titania-polyelectrolyte nanotubes were also successfully prepared by sequential LbL deposition of titanium (IV) bis(ammonium lactato) dihydroxide (TALH) and poly(ethylenimine) (PEI) inside the cylindrical pores of a TEPC templates, followed by calcination at various temperatures. 53 TALH is stable in neutral solutions 54 and represents an excellent candidate for the preparation of titania-based thin films using aqueous chemistry.…”
Section: Formation Of Heterostructured Nanotubes Via Lbl Assembly Of ...mentioning
confidence: 99%
“…It has been demonstrated that the biomimetic synthesis provides a unique shortcut to functional materials with designed properties. [52][53][54][55] The currently developed approach is of great generality for the self-assembly of various functional molecules or guest substances onto the titania gel lm activated surface of cellulose materials, and it provides a pathway to accomplish the combination of the internal excellent properties of natural cellulose materials (e.g., large surface area, exibility, nontoxicity, biodegradability etc.) and the functionalities of guest species to fabricate various advanced cellulose-based functional materials.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted cell detachment is of significant interest and presents new capabilities and opportunities in areas such as biomedicine, cell biology, implantable biomaterials, and tissue engineering 1 2 3 4 5 6 . Among the variety of available techniques for targeted cell detachment (regulation of cell apoptosis) 7 8 9 10 11 , the layer-by-layer (LbL) assembly method plays a pioneering role, because it possesses extraordinary advantages for applications of regulating cell growth and apoptosis including easy formation of supported films, flexible control over structures, combination of various ingredients, adjustable physical properties 12 13 14 15 . A wide variety of functional materials such as biological polymers and inorganic nanoparticles can be readily combined for achieving properties corresponding to each type of materials and integrated functionalities, thus leading to the control over mechanical strength and biocompatibility of LbL assembled films 16 17 18 19 .…”
mentioning
confidence: 99%